CIVIL LIABILITY OF BUSINESS OPERATORS IN TRADITIONAL HEALTH SERVICES THAT CAUSE HARM TO CLIENTS - Teguh Adi Partama; Carolina; Imam Ropii; Marsudi Dedi Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Traditional health services are increasingly sought by the public as an alternative or complement to modern medical treatment. Although these practices are recognized within Indonesia’s national legal system, existing regulations remain incomplete, particularly concerning civil law liability when harm occurs to clients. This study analyzes the forms of liability borne by business actors, including liability arising from tort and default, as well as mechanisms for dispute resolution and compensation. Employing a normative juridical method, this research integrates statutory, conceptual, and case approaches. Data were collected through literature studies and analyzed qualitatively. The findings indicate that business actors may be held legally accountable under Article 1365 and Article 1239 of the Indonesian Civil Code. Liability may result in both material and immaterial compensation, provided in accordance with applicable positive law in Indonesia. Strengthening regulations on traditional health services is therefore essential to ensure legal certainty and protection for consumers while maintaining professional accountability.